Cardiac volume overload and pulmonary hypertension in long-term follow-up of patients with a transjugular intrahepatic portosystemic shunt - Wannhoff, Andreas; Wenz, Theresa; Weiss, Celine; Friedrich, Kilian; Rupp, Christian; Antoni, Christoph Helmer; Stampfl, Ulrike; Schemmer, Peter; Stremmel, Wolfgang; Weiss, Karl Heinz; Radeleff, Boris; Katus, Hugo; et al. (Alimentary pharmacology & therapeutics, 2016)
Background Transjugular intrahepatic portosystemic shunt (TIPSS) cause haemodynamic changes in patients with cirrhosis, yet little is known about long-term cardiopulmonary outcomes. Aim To evaluate the long-term cardiopulmonary outcome after TIPSS. Methods We evaluated cardiopulmonary parameters including echocardiography during long-term follow-up after TIPSS. Results at 1-5 years after TIPSS were compared to those of cirrhotic controls. Pulmonary hypertension (PH) diagnoses rates were included. Endothelin 1, thromboxane B2 and serotonin were measured. Results We found significant differences 1-5 years after TIPSS compared to pre-implantation values: median left atrial diameter (LAD) increased from 37 mm [interquartile range (IQR): 33-43] to 40 mm (IQR: 37-47, P = 0.001), left ventricular end-diastolic diameter (LV-EDD) increased from 45 mm (range: 41-49) to 48 mm (IQR: 45-52, P < 0.001), pulmonary artery systolic pressure (PASP) increased from 25 mmHg (IQR: 22-33) to 30 mmHg (IQR: 25-36, P = 0.038). Comparing results 1-5 years post-implantation to the comparison cohort revealed significantly higher (P < 0.05) LAD, LV-EDD and PASP values in TIPSS patients. PH prevalence was higher in the shunt group (4.43%) compared to controls (0.91%, P = 0.150). Thromboxane B2 levels correlated with PASP in the TIPSS cohort (P = 0.033). There was no transhepatic gradient observed for the vasoactive substances analysed. Conclusions TIPSS placement is accompanied by long-term cardiovascular changes, including cardiac volume overload, and is associated with an increased rate of pulmonary hypertension. The need for regular cardiac follow-up after TIPSS requires further evaluation.